Application of Business Ethics in Relation to Buyer Trust from a Sharia Perspective in Sape District - Rizal, Syahrul; Parakkasi, Idris; Wahab, Abdul (Jurnal Ilmu Manajemen Profitability, 2025)
This study examines the application of Islamic business ethics and its impact on buyer trust in modern and traditional markets in Sape District, Bima Regency, West Nusa Tenggara. It aims to understand how business actors perceive and implement ethical principles in their transactions. Using qualitative field research with descriptive analysis, the study employs normative theological, sociological, and phenomenological approaches. Data sources include primary data from observations and interviews, as well as secondary data from literature. Findings show that most business actors in both modern and traditional markets have a general understanding of business ethics and apply them to some extent. Many traders indirectly practice ethical behavior in transactions. However, the full implementation of Islamic business ethics—honesty, justice, trustworthiness, and tolerance—remains inconsistent. Many business actors still prioritize profit over ethical considerations, focusing on financial gain rather than the spiritual value or blessings of fair business practices. This gap highlights the need for greater awareness and education on sharia business ethics. Strengthening ethical training programs and regulatory frameworks can encourage business actors to integrate these principles more consistently, fostering a trustworthy and sustainable market environment.